Sleep disturbance and hypertension mediated by systemic inflammatory response index in NHANES - Zhaoxing Cao; Fangfang Zhuo; Fei Yan; Xi Hu; Guiling Xia; Cheng Huang; Ting Lu; Zhipeng Pu; Runze Huang; Zhangrong Chen (Scientific Reports)
Abstract Both hypertension and sleep disturbance have been closely linked to inflammation. However, the specific role of inflammation in the relationship between sleep disturbance and hypertension remains unclear. We investigated the pairwise associations among a novel inflammatory marker (systemic immune inflammation index ), sleep disturbance, and hypertension in a powerful, racially diverse sample (n = 23,414) from the 2005–2020 National Health and Nutrition Examination Survey (NHANES). We found that participants with high blood pressure and/or sleep disorders had higher levels of Systemic Immune-Inflammatory Index (SII) than those without hypertension or sleep disorders.SII slightly but significantly mediated the relationship between sleep disturbance and hypertension in males but not in females, after adjusting for all covariates (proportion mediate [PM], 1.36%; total effect [TE], 0.0931; direct effect [ADE], 0.0917; verage causal mediation effects [ACME] = 0.0013 [95% CI = 0.0004–0.0024], p = 0.002, in males. Our research showed that SII, sleep disturbance, and hypertension are related. Increased SII levels slightly mediated the association between sleep disturbance and hypertension.